Pendampingan Pembuatan Minuman Sehat Instan Kering Dari Bahan Alami Tumbuhan Di Desa Bingkat Kecamatan Pegajahan Kabupaten Serdang Bedagai Sumatera Utara - Andilala; Rina Chairani Lubis; Juliana Sion Sihombing; Fatmazahra; Siti Nurdiana; Yusuf Hamdani Sinaga (STIKES Columbia Asia Medan, 2026)
Mothers in Bingkat Village have daily activities as housewives and participate with their husbands as farmers and livestock, as well as social activities of village and religious organizations, not to the extent of family economic improvement activities. Making instant dry healthy drinks from natural ingredients, such as ginger or other plants around the house is very easy, simple tools, low cost, and has economic value. The target of the activity is to provide assistance in making dry instant healthy drinks. Based on this, it is considered necessary to provide assistance in making dry instant healthy drinks. Assistance is not only manufacturing, but also good product packaging and counseling on the marketing direction of products made by the people of Bingkat Village. This instant dry healthy drink product from natural ingredients has a selling value, so it is hoped that it can increase family income and welfare.